2019
DOI: 10.1038/s41598-019-42087-z
|View full text |Cite
|
Sign up to set email alerts
|

Dex-CSDH randomised, placebo-controlled trial of dexamethasone for chronic subdural haematoma: report of the internal pilot phase

Abstract: The Dex-CSDH trial is a randomised, double-blind, placebo-controlled trial of dexamethasone for patients with a symptomatic chronic subdural haematoma. The trial commenced with an internal pilot, whose primary objective was to assess the feasibility of multi-centre recruitment. Primary outcome data collection and safety were also assessed, whilst maintaining blinding. We aimed to recruit 100 patients from United Kingdom Neurosurgical Units within 12 months. Trial participants were randomised to a 2-week course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…An internal pilot randomized trial, which enrolled 100 patients at seven trial sites, confirmed the operational feasibility of the overall trial. 11 As prespecified, the pilot phase did not aim to assess efficacy or reestimate the sample size, and these patients were included in the final analysis.…”
Section: Trial Design and Oversightmentioning
confidence: 99%
“…An internal pilot randomized trial, which enrolled 100 patients at seven trial sites, confirmed the operational feasibility of the overall trial. 11 As prespecified, the pilot phase did not aim to assess efficacy or reestimate the sample size, and these patients were included in the final analysis.…”
Section: Trial Design and Oversightmentioning
confidence: 99%
“…In addition, in the hematoma of patients with CSDH, the activation of plasmin's leads to a significant increase in thrombosis regulatory protein, and then forms a state of high fibrinolysis, which promotes blood vessel leakage leading to promote CSDH progression (36). Based on the understanding of inflammation, angiogenesis, and hyperfibrinolysis in the development of CSDH, Several related studies have investigated the role of various medical adjuncts, such as atorvastatin (37,38), dexamethasone (15,39,40), TXA (4,12,14,18,20,(40)(41)(42)(43), etc. in reducing their postoperative recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…This was achieved with acceptable adverse effects related to considerable period of glucocorticoid therapy with strict vigilance of patient during this therapy. When pilot study on Dex-CSDH was published in 2019 with its inception in 2015 [16], the author was enthusiastically propelled to contemplate similar study in the country of his medical practice. The author wanted to conduct a randomized controlled trial comparing the efficacy and safety of Dexamethasone therapy with surgical drain of subdural collection.…”
Section: Discussionmentioning
confidence: 99%